Non-stoichiometric long-afterglow transparent ceramic and preparation method thereof

By using garnet matrix and ion co-doping technology in long afterglow transparent ceramics, combined with vacuum sintering and thermal isostatic pressure sintering, the problem of afterglow attenuation of ceramics in high temperature environments is solved, and ceramic preparation with high transmittance and long afterglow time is achieved.

CN119551985AActive Publication Date: 2025-03-04XUZHOU NORMAL UNIVERSITY +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411759735.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-04
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The existing long afterglow transparent ceramics are prone to greatly attenuation in high temperature environments and their residual glare duration and brightness, and have poor water resistance, which limits their practical application.

Method used

Garnet is used as the matrix, and long afterglow transparent ceramics with non-uniform stoichiometric ratios are prepared by matrix regulation method and ion co-doping method, and vacuum sintering method combined with thermal isostatic pressure sintering method is used to improve the transmittance and afterglow time of the ceramics.

Benefits of technology

The transmittance of ceramics at 800nm ​​reaches 78-85%, and the afterglow time is extended to 15-30 hours, which significantly improves the optical quality and afterglow performance of ceramics, and solves the attenuation problem in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551985A_ABST
    Figure CN119551985A_ABST
Patent Text Reader

Abstract

The invention discloses a non-stoichiometric long-afterglow transparent ceramic and a preparation method thereof. The chemical general formula of the ceramic is (RE1-xCex) 3 (Al1-yCry) 2Ga3 + zO12, RE is selected from one of Lu, Y and Gd, and the value ranges of x, y and z are as follows: 0.001 < = x < = 0.005, 0.0005 < = y < = 0.02, and 0.01 < = z < = 0.15. The ceramic is prepared by combining a vacuum sintering method with a hot isostatic pressing method. According to the invention, garnet is adopted as a matrix, a matrix regulation and control method is adopted, and an ion co-doping means is combined, so that the transmittance of the prepared ceramic can reach 78-85%, and the afterglow time is improved by 720-1080 minutes compared with that of Ce ion single-doped long afterglow transparent ceramic, is improved by 180-300 minutes compared with that of ceramic which is not subjected to HIP sintering, and is improved by 180-480 minutes compared with that of stoichiometric ratio ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of transparent ceramic preparation, and in particular to a non-stoichiometric long afterglow transparent ceramic and a preparation method thereof. Background Art

[0002] The phenomenon that a material continues to emit light after it stops absorbing external excitation energy is called long afterglow luminescence. Materials that can achieve long afterglow luminescence are called long afterglow materials. Visible light long afterglow materials have been widely used as emergency indicator lighting signs in public places, highways, airports, dangerous areas and other scenarios. Especially in the "9.11" incident, long afterglow materials played an important role in emergency evacuation. SrAl2O4:Eu with excellent afterglow performance 2+ ,Dy 3+ Long afterglow powder has been commercialized, but its water resistance is poor, and in high temperature environment, the afterglow duration and afterglow brightness are prone to significant attenuation, which limits its practical application.

[0003] Long afterglow transparent ceramics have the advantages of good water resistance, high and low temperature resistance, corrosion resistance, and excellent mechanical properties. Its high light transmittance enables it to be effectively excited in the bulk space, thereby greatly enhancing the ceramic's ability to capture carriers and luminescence uniformity. With its unique "volume effect", the afterglow performance can be flexibly adjusted by changing the thickness of the ceramic. 5-x Ga x O 12 (x=0,1,2,3,4) transparent ceramics are one of the most promising transparent ceramics with long afterglow luminescence potential. In the research of YAG long afterglow transparent ceramics, the Ueda group of Kyoto University (XU J,UEDA J,KUROISHI K,et al.Fabrication of Ce 3+ -Cr 3+ co-doped yttrium aluminiumgallium garnet transparent ceramic phosphors with super long persistent luminescence[J].Scripta Mater,2015,102:47-50.) Y3Al2Ga3O 12:Ce,Cr, the afterglow time of 2.1mm thick ceramics after 460nm blue light excitation for 5min can reach 846min, and the transmittance of 1.4mm thick ceramics at 800nm ​​is 72%. The raw material powder has high purity and good powder quality, but few purchase channels and high prices. In addition, there is no reliable solution to the volatilization problem of Ga under vacuum and high temperature, so the preparation of this ceramic lacks repeatability. Li Jiang's group (LIU Q, WANG WL, DAI ZF, et al. Fabrication and long persistent luminescence of Ce 3+ -Cr 3+ co-doped yttrium aluminum gallium garnet transparent ceramics[J].J Rare Earth,2022,40(11):1699-1705.) 3+ Ion doping concentration of Y3Al2Ga3O 12 :Ce 3+ ,Cr 3+ Long afterglow transparent ceramics, including Ce 3+ The initial afterglow brightness of the ceramic with a doping concentration of 0.2% after being excited by 365nm violet light for 5 minutes can reach 3614mcd / m 2 Under the same excitation conditions, the initial afterglow brightness of the ceramic annealed in air atmosphere is 4424mcd / m 2 , the afterglow time can reach 865min. The volatilization of Ga is effectively alleviated by air sintering, but the transmittance of the ceramic at 800nm ​​is only 28%, and its service performance is poor. When facing harsh environments, long afterglow transparent ceramics with high optical quality can rely on their excellent mechanical properties, corrosion resistance, and high temperature resistance to ensure their stable afterglow performance and extend their service life. Therefore, this field urgently needs a long afterglow transparent ceramic with high light transmittance and long afterglow time. Summary of the invention

[0004] The purpose of the present invention is to provide a non-stoichiometric long afterglow transparent ceramic with good light transmittance and long afterglow time.

[0005] Another object of the present invention is to provide a method for preparing the above-mentioned non-stoichiometric long afterglow transparent ceramic, which is easy to operate and can be industrialized.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] In one aspect, the present invention provides a non-stoichiometric long afterglow transparent ceramic, the general chemical formula of which is:

[0008] (RE 1-x Ce x )3(Al 1-y Cr y )2Ga 3+z O 12 ,

[0009] RE is selected from one of Lu, Y, and Gd, and the value ranges of x, y, and z are: 0.001≤x≤0.005, 0.0005≤y≤0.02, 0.01≤z≤0.15.

[0010] The ceramic has a transmittance of 78-85% at 800nm, a luminous wavelength of 480-600nm, and an afterglow time of 15-30 hours.

[0011] On the other hand, the present invention also provides a method for preparing the above-mentioned non-stoichiometric long afterglow transparent ceramic, which adopts a vacuum sintering method combined with hot isostatic pressing, and specifically comprises the following steps:

[0012] (1) According to the chemical formula (RE 1-x Ce x )3(Al 1-y Cr y )2Ga 3+z O 12 RE2O3, Al2O3, Ga2O3, CeO2, and Cr2O3 with a stoichiometric ratio of each element and a purity greater than 99.99% are used as raw material powders, and the raw material powders, sintering aids, and ball milling media are mixed in a certain proportion to obtain a mixed slurry; wherein RE is selected from one of Lu, Y, and Gd, 0.001≤x≤0.005, 0.0005≤y≤0.02, and 0.01≤z≤0.15;

[0013] (2) drying the mixed slurry obtained in step (1) in a drying oven, sieving the dried mixed powder, and calcining the mixed powder in a muffle furnace under air atmosphere;

[0014] (3) placing the powder calcined in step (2) into a mold for dry pressing, and then cold isostatic pressing;

[0015] (4) placing the green blank obtained in step (3) in a vacuum furnace for sintering;

[0016] (5) The ceramic obtained in step (4) is subjected to hot isostatic pressing and sintering, and after cooling to room temperature, double-sided polishing is performed to obtain the long afterglow transparent ceramic.

[0017] Preferably, in step (1), the ball milling speed is 170 to 250 r / min, and the ball milling time is 10 to 16 h.

[0018] Preferably, in step (1), the sintering aid is composed of 0.5-1.2wt.% of tetraethyl orthosilicate or 0.03-0.1wt.% of magnesium oxide, the added amount of the sintering aid is 0.1-1% of the total mass of the raw material powder, the ball milling medium is anhydrous ethanol, and the mass volume ratio of the raw material powder to the ball milling medium is 1g:(2-4)mL.

[0019] Preferably, in step (2), the drying time is 15 to 30 hours and the drying temperature is 80 to 90°C.

[0020] Preferably, in step (2), the mesh size of the sieve is 60 to 200 meshes.

[0021] Preferably, in step (2), the calcination temperature is 600-900° C., and the calcination time is 5-8 hours.

[0022] Preferably, in step (3), the cold isostatic pressing holding pressure is 150 to 200 MPa, and the holding time is 200 to 400 s.

[0023] Preferably, in step (4), the sintering temperature is 1520-1750°C, the holding time is 8-24h, and the sintering vacuum is not less than 10 -3 Pa.

[0024] Preferably, in step (5), the hot isostatic pressing sintering pressure is 120-200 MPa, the sintering temperature is 1550-1780° C., the holding time is 2-4 h, and the heating rate is 1.5-3.0° C. / min.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] (1) The present invention uses garnet as a matrix, adopts a matrix control method, and combines ion co-doping to prepare a ceramic with a transmittance of 78-85%. The afterglow time is increased by 720-1080 minutes compared to long afterglow transparent ceramics doped with Ce ions alone.

[0027] (2) The sintering method adopted in the present invention is a vacuum sintering method combined with hot isostatic pressing. The inert gas in hot isostatic pressing is conducive to the generation of oxygen vacancies, which can improve the afterglow performance of the transparent ceramic. The afterglow time is increased by 180 to 300 minutes compared with the ceramics not sintered by HIP.

[0028] (3) The present invention adopts a non-stoichiometric ratio approach, and the appropriate increase in the amount of Ga effectively alleviates the volatilization under vacuum and high temperature, and improves the optical quality and afterglow time of the ceramic. The transmittance of the prepared ceramic is increased by 5-15% compared with the stoichiometric ratio ceramic, and the afterglow time is increased by 180-480 minutes compared with the stoichiometric ratio ceramic.

[0029] (4) The sintering aid used in the present invention is tetraethyl orthosilicate. An appropriate amount of tetraethyl orthosilicate added can effectively improve the densification of the ceramic and regulate the valence state of the transition metal ion Cr, thereby improving the afterglow performance of the ceramic. The afterglow time of the prepared ceramic is increased by 600 to 900 minutes compared to the ceramic without the addition of tetraethyl orthosilicate. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the XRD spectrum of the long afterglow transparent ceramic prepared in Example 4 of the present invention.

[0031] Figure 2 1 and 2 are transmittance curves of the long afterglow transparent ceramics prepared in Example 4 and Comparative Example 4 of the present invention.

[0032] Figure 3 This is the afterglow emission spectrum of the long afterglow transparent ceramic prepared in Example 4 of the present invention.

[0033] Figure 4 The afterglow decay curves of the long afterglow transparent ceramics prepared in Example 4, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.

[0035] Unless otherwise stated, the raw materials used in the following examples are all commercially available products.

[0036] Example 1

[0037] (1) According to the chemical formula (Lu 0.999 Ce 0.001 )3(Al 0.9995 Cr 0.0005 )2Ga 3.05 O 12 Weigh 100 g of raw material powder in the stoichiometric ratio of each element; use 200 mL of anhydrous ethanol as a ball milling medium and 600 μL of tetraethyl orthosilicate as a sintering aid, place the accurately weighed raw material powder in a ball milling jar and mill at 170 r / min for 15 hours to obtain a uniformly mixed slurry, place the ball-milled slurry in an oven at 80°C to dry for 15 hours, pass through an 80-mesh sieve, and place it in a muffle furnace and calcine at 800°C for 8 hours;

[0038] (2) dry pressing the calcined powder at a pressure of 10 MPa for 180 seconds, and cold isostatically pressing at 150 MPa for 360 seconds to obtain a ceramic green body;

[0039] (3) The ceramic blank is placed in a vacuum furnace for sintering at a temperature of 1520°C, a holding time of 8 hours, and a sintering vacuum degree of 10 -3 Pa;

[0040] (4) The ceramics obtained by vacuum sintering were placed in a hot isostatic pressing furnace for HIP sintering, wherein the argon pressure was 120 MPa, the sintering temperature was 1550°C, the holding time was 120 min, the heating rate was 1.5°C / min, the cooling rate was 1.5°C / min, and the double-sided polishing was performed to 2 mm to obtain the desired ceramics.

[0041] The obtained transparent ceramic has a transmittance of 78% at 800nm ​​and an afterglow time of up to 1080 minutes at 495nm.

[0042] Example 2

[0043] (1) According to the chemical formula (Y 0.997 Ce 0.003 )3(Al 0.999 Cr 0.001 )2Ga 3.05 O 12 Weigh 100 g of raw material powder in the stoichiometric ratio of each element; use 220 mL of anhydrous ethanol as a ball milling medium and 650 μL of tetraethyl orthosilicate as a sintering aid, place the accurately weighed raw material powder in a ball mill at 180 r / min for 12 hours to obtain a uniformly mixed slurry, place the ball-milled slurry in an oven at 82°C to dry for 16 hours, pass through an 80-mesh sieve, and place it in a muffle furnace and calcine at 800°C for 8 hours;

[0044] (2) dry pressing the calcined powder at a pressure of 20 MPa for 90 seconds, and cold isostatically pressing at 150 MPa for 360 seconds to obtain a ceramic green body;

[0045] (3) The ceramic blank is placed in a vacuum furnace for sintering at a temperature of 1560°C, a holding time of 10 h, and a sintering vacuum degree of 10 -3 Pa;

[0046] (4) placing the vacuum sintered ceramic in a hot isostatic pressing furnace for HIP sintering, wherein the argon pressure is 140 MPa, the sintering temperature is 1580° C., the holding time is 120 min, the heating rate is 1.5° C. / min, the cooling rate is 1.5° C. / min, and the double-sided polishing is performed to 2 mm to obtain the desired ceramic;

[0047] The transmittance of the obtained transparent ceramic is 80% at 800nm, and the afterglow time at 515nm band can reach 1250 minutes.

[0048] Example 3

[0049] (1) According to the chemical formula (Gd 0.995 Ce 0.005 )3(Al 0.995 Cr 0.005 )2Ga 3.1 O 12 Weigh 100 g of raw material powder in the stoichiometric ratio of each element; use 200 mL of anhydrous ethanol as a ball milling medium and 700 μL of tetraethyl orthosilicate as a sintering aid, place the accurately weighed raw material powder in a ball mill at 200 r / min for 10 hours to obtain a uniformly mixed slurry, place the ball-milled slurry in an oven at 85°C to dry for 17 hours, pass through an 80-mesh sieve, and place it in a muffle furnace and calcine at 800°C for 8 hours;

[0050] (2) dry pressing the calcined powder at a pressure of 20 MPa for 90 seconds, and cold isostatically pressing at 150 MPa for 360 seconds to obtain a ceramic green body;

[0051] (3) The ceramic blank is placed in a vacuum furnace for sintering at a temperature of 1580°C, a holding time of 10 h, and a sintering vacuum degree of 10 -3 Pa;

[0052] (4) placing the vacuum sintered ceramic in a hot isostatic pressing furnace for HIP sintering, wherein the argon pressure is 150 MPa, the sintering temperature is 1600° C., the holding time is 180 min, the heating rate is 2.0° C. / min, the cooling rate is 2.0° C. / min, and the double-sided polishing is performed to 2 mm to obtain the desired ceramic;

[0053] The transmittance of the obtained transparent ceramic is 82% at 800nm, and the afterglow time at 550nm band can reach 1440 minutes.

[0054] Example 4

[0055] (1) According to the chemical formula (Y 0.995 Ce 0.005 )3(Al 0.995 Cr 0.005 )2Ga 3.15 O 12Weigh 100 g of raw material powder in the stoichiometric ratio of each element; use 200 mL of anhydrous ethanol as a ball milling medium and 720 μL of tetraethyl orthosilicate as a sintering aid, place the accurately weighed raw material powder in a ball mill at 220 r / min for 12 hours to obtain a uniformly mixed slurry, place the ball-milled slurry in an oven at 88°C to dry for 18 hours, pass through an 80-mesh sieve, and place it in a muffle furnace and calcine at 800°C for 8 hours;

[0056] (2) dry pressing the calcined powder at a pressure of 20 MPa for 90 seconds, and cold isostatically pressing at 160 MPa for 360 seconds to obtain a ceramic green body;

[0057] (3) The ceramic blank is placed in a vacuum furnace for sintering at a temperature of 1600°C, a holding time of 10 h, and a sintering vacuum degree of 10 -3 Pa;

[0058] (4) The ceramics obtained by vacuum sintering are placed in a hot isostatic pressing furnace for HIP sintering, wherein the argon pressure is 150 MPa, the sintering temperature is 1620°C, the holding time is 180 min, the heating rate is 3°C / min, the cooling rate is 3°C / min, and the double-sided polishing is performed to 2 mm to obtain the desired ceramics.

[0059] Comparative Example 1

[0060] The preparation method of the ceramic is basically the same as that of Example 4, except that the Ce-doped 3+ , the chemical formula is (Y 0.995 Ce 0.005 )3Al2Ga 3.15 O 12 .

[0061] Comparative Example 2

[0062] The method for preparing the ceramic is substantially the same as that of Example 4, except that HIP sintering is not used.

[0063] Comparative Example 3

[0064] The preparation method of the ceramic is substantially the same as that of Example 4, except that the sintering aid TEOS is not added.

[0065] Comparative Example 4

[0066] The preparation method of the ceramic is basically the same as that of Example 4, except that the ceramic is prepared according to the chemical formula (Y 0.995 Ce 0.005 )3(Al 0.995 Cr 0.005 )2Ga3O 12 Weigh the raw material powder according to the stoichiometric ratio of each element.

[0067] Figure 1 (Y prepared in Example 4 of the present invention 0.995 Ce 0.005 )3(Al 0.995 Cr 0.005 )2Ga 3.15 O 12 XRD spectrum of long afterglow transparent ceramics. The diffraction peaks of the prepared ceramic samples are consistent with the standard card PDF of YAGG.

[0068] Figure 2 Prepared as Example 4 (Y 0.995 Ce 0.005 )3(Al 0.995 Cr 0.005 )2Ga 3.15 O 12 Long afterglow transparent ceramics and comparative example 4 (Y 0.995 Ce 0.005 )3(Al 0.995 Cr 0.005 )2Ga3O 12 The transmittance curve of long afterglow transparent ceramics shows that the transmittance of the former is 85% at 800nm, while the transmittance of the latter is only 70% at 800nm.

[0069] Figure 3 Prepared as Example 4 (Y 0.995 Ce 0.005 )3(Al 0.995 Cr 0.005 )2Ga 3.15 O 12 The emission spectrum of long afterglow transparent ceramics has strong luminescence in the range of 480-600nm, and the luminescence peak is near 515nm.

[0070] Figure 4 The afterglow attenuation curves of the long afterglow transparent ceramics prepared in Example 4, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were measured using an afterglow tester. After stopping the excitation of the radiation source (blue light 460nm), the (Y 0.995 Ce 0.005 )3(Al 0.995 Cr 0.005 )2Ga 3.15 O 12 The afterglow time of long afterglow transparent ceramics can reach 1900 minutes, and the initial brightness is 6235mcd / m 2 ; Comparative Example 1 prepared (Y 0.995 Ce 0.005 )3Al2Ga 3.15 O 12 The afterglow time of long afterglow transparent ceramic is 610 minutes and the initial brightness is 3820mcd / m2 ; Comparative Example 2 prepared (Y 0.995 Ce 0.005 )3(Al 0.995 Cr 0.005 )2Ga 3.15 O 12 The afterglow time of the long afterglow transparent ceramic (not sintered by HIP) is 1650 minutes and the initial brightness is 5980mcd / m 2 ; Comparative Example 3 prepared (Y 0.995 Ce 0.005 )3(Al 0.995 Cr 0.005 )2Ga 3.15 O 12 The afterglow time of the long afterglow transparent ceramic (without the sintering aid TEOS) is 780 minutes, and the initial brightness is 4386mcd / m 2 ; Comparative Example 4 prepared (Y 0.995 Ce 0.005 )3(Al 0.995 Cr 0.005 )2Ga3O 12 The afterglow time of long afterglow transparent ceramic is 1580 minutes and the initial brightness is 5380mcd / m 2 .

[0071] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. A non-stoichiometric long afterglow transparent ceramic, characterized in that: The general chemical formula of the ceramic is: (RE 1-x What x )3(Al 1-y -R y )2Ga 3+z A 12 , RE is selected from one of Lu, Y, and Gd, and the value ranges of x, y, and z are: 0.001≤x≤0.005, 0.0005≤y≤0.02, 0.01≤z≤0.

15.

2. A method for preparing the non-stoichiometric long afterglow transparent ceramic according to claim 1, characterized in that: The vacuum sintering method combined with hot isostatic pressing is adopted, which specifically includes the following steps: (1) According to the chemical formula (RE 1-x Ce x )3(Al 1-y Cr y )2Ga 3+z O 12 RE2O3, Al2O3, Ga2O3, CeO2, and Cr2O3 with a stoichiometric ratio of each element and a purity greater than 99.99% are used as raw material powders, and the raw material powders, sintering aids, and ball milling media are mixed in a certain proportion to obtain a mixed slurry; wherein RE is selected from one of Lu, Y, and Gd, 0.001≤x≤0.005, 0.0005≤y≤0.02, and 0.01≤z≤0.15; (2) drying the mixed slurry obtained in step (1) in a drying oven, sieving the dried mixed powder, and calcining the mixed powder in a muffle furnace under air atmosphere; (3) placing the powder calcined in step (2) into a mold for dry pressing, and then cold isostatic pressing; (4) placing the green blank obtained in step (3) in a vacuum furnace for sintering; (5) The ceramic obtained in step (4) is subjected to hot isostatic pressing and sintering, and after cooling to room temperature, double-sided polishing is performed to obtain the long afterglow transparent ceramic.

3. The method for preparing non-stoichiometric long afterglow transparent ceramic according to claim 2, characterized in that: In step (1), the ball milling speed is 170-250 r / min, and the ball milling time is 10-16 h.

4. The method for preparing non-stoichiometric long afterglow transparent ceramic according to claim 2, characterized in that: In step (1), the sintering aid is composed of 0.5-1.2wt.% of ethyl orthosilicate or 0.03-0.1wt.% of magnesium oxide, the added amount of the sintering aid is 0.1-1% of the total mass of the raw material powder, the ball milling medium is anhydrous ethanol, and the mass volume ratio of the raw material powder to the ball milling medium is 1g: (2-4)mL.

5. The method for preparing non-stoichiometric long afterglow transparent ceramics according to claim 2, characterized in that: In step (2), the drying time is 15 to 30 hours and the drying temperature is 80 to 90°C.

6. The method for preparing non-stoichiometric long afterglow transparent ceramic according to claim 2, characterized in that: In step (2), the mesh size of the sieve is 60 to 200 meshes.

7. The method for preparing non-stoichiometric long afterglow transparent ceramics according to claim 2, characterized in that: In step (2), the calcination temperature is 600-900° C., and the calcination time is 5-8 hours.

8. The method for preparing non-stoichiometric long afterglow transparent ceramics according to claim 2, characterized in that: In step (3), the cold isostatic pressing holding pressure is 150 to 200 MPa, and the holding time is 200 to 400 s.

9. The method for preparing non-stoichiometric long afterglow transparent ceramics according to claim 2, characterized in that: In step (4), the sintering temperature is 1520-1750°C, the holding time is 8-24 hours, and the sintering vacuum degree is not less than 10 -3 Pa.

10. The method for preparing non-stoichiometric long afterglow transparent ceramics according to claim 2, characterized in that: In step (5), the hot isostatic pressing sintering pressure is 120-200 MPa, the sintering temperature is 1550-1780° C., the holding time is 2-4 h, and the heating rate is 1.5-3.0° C. / min.

Citation Information

Patent Citations

  • Preparation method of yttrium-aluminum garnet single crystal

    CN102409391A

  • Ytterbium, lutecium, gadolinium and gallium doped garnet laser crystal, preparation method and applications thereof

    CN103397385A

  • Method for preparing yttrium aluminium garnet transparent ceramic with composite structure

    CN103626487A

  • Method for increasing solid solubility of doping ion in YAG-based transparent ceramic

    CN110590353A

  • Preparation method of assembly type light-emitting oscillation marked line

    CN113213934A